Contr¡butions (o Toledo flora. 1 - Marcos Samaniego, Nieves; Bornet Carrasquilla, Carmen; González Aguejas, Inmaculada (Botanica Complutensis, 1989)
MARCOs SAMANIEGO, N.: GONZÁLEZ AGEJAS, 1.. & BONET (ÁRR\SCI III A. C. 1989. Contributions to Toledo Flora. 1. Bat (omplu¡ensis 15: 233-232 Sebultes & Sehultes fil.. Centaurea triumfetti AII. subsp. lingulata (Lag.) Dostál.
Keywords: Vascular plants; Toledo Spain 234 Marcos Samaniego; N et aL